The effect of red wine consumption on health - Rzeszutko, Mateusz; Szponarowicz, Patrycja; Raczkiewicz, Przemysław; Snopkowski, Bartosz; Skrętowicz, Mateusz; Korzec, Tomasz; Sosnowski, Jakub; Panek, Eliasz; Jasłowski, Damian; Panasiuk, Dominika (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: The impact of red wine consumption on the human body has been the case of research by many scientists. The aim of this study is to review the literature, present the most important research findings, and summarize the current knowledge about wine and other alcoholic beverages consumption. Methodology and materials: A review of the available literature in the PubMed and Google Scholar databases using keywords such as "red wine," "cardiovascular disease," "red wine’’ and ‘’health benefits." State of knowledge: Red wine is an alcohol containing many active flavonoid and non-flavonoid substances that have multi-directional effects, including functioning as natural "sweepers" of free radicals. Ethanol itself, in moderate amounts, exhibits certain cardioprotective effects. Summary: Numerous studies indicate a positive effect of moderate red wine consumption in the prevention of cardiovascular diseases. It has also been shown to reduce the risk of death regardless of the cause.